Respuesta :

Answer:

x = 6 , y = 0   (x , y) = (6 , 0)

x = 12, y = 3   (x , y) = (12 , 3)

x = 24, y = 9   (x , y) = (24 , 9)

Step-by-step explanation:

Simply plug in a x, and find a y that would make the equation true:

When x = 6:

6 - 2y = 6

6 (-6) - 2y = 6 (-6)

-2y = 0

(-2y)/-2 = (0)/-2

y = 0

When x = 6, y = 0    (x , y) = (6 , 0)

When x = 12:

12 - 2y = 6

12 (-12) -2y = 6 (-12)

-2y = -6

(-2y)/-2 = (-6)/-2

y = 3

When x = 12, y = 3   (x , y) = (12 , 3)

When x = 24:

24 - 2y = 6

24 (-24) - 2y = 6 (-24)

-2y = -18

(-2y)/-2 = (-18)/-2

y = 9

When x = 24, y = 9   (x , y) = (24 , 9)

~